STATISTICAL INTERACTIONS AND BAYES ESTIMATION OF LOG ODDS IN CASE-CONTROL STUDIES - Satagopan, Jaya M. (Stat Methods Med Res, 2015)
This paper is concerned with the estimation of the logarithm of disease odds (log odds) when evaluating two risk factors, whether or not interactions are present. Statisticians define interaction as a departure from an additive model on a certain scale of measurement of the outcome. Certain interactions, known as removable interactions, may be eliminated by fitting an additive model under an invertible transformation of the outcome. This can potentially provide more precise estimates of log odds than fitting a model with interaction terms. In practice, we may also encounter non-removable interactions. The model must then include interaction terms, regardless of the choice of the scale of the outcome. However, in practical settings, we do not know at the outset whether an interaction exists, and if so whether it is removable or non-removable. Rather than trying to decide on significance levels to test for the existence of removable and non-removable interactions, we develop a Bayes estimator based on a squared error loss function. We demonstrate the favorable bias-variance trade-offs of our approach using simulations, and provide empirical illustrations using data from three published endometrial cancer case-control studies. The methods are implemented in an R program, available freely at http://www.mskcc.org/biostatistics/~satagopj.